Perception of Limitations by Individuals Threatened with Social Exclusion upon Entering Employment: Report on a Study of Individuals with Chronic Mental Illnesses - Dobrowolska, Małgorzata; Paruzel-Czachura, Mariola; Stasila-Sierdzka, Marta; Sikora, Jagoda (European Journal of Economics and Business Studies, 2018)
The paper presents the results of qualitative research involving a group of 30 disabled persons, suffering from chronic mental conditions, and in most cases staying at residential care homes. The authors conducted targeted free interviews with an interview outline, i.e. a list of the required information. The research was conducted among occupationally active but unemployed individuals, i.e. ones who declared the willingness to work. The sample for the study was selected using purposive sampling: all the subjects were using the services of an employment counsellor at the time.The aim of the free interviews was to identify the barriers making it difficult for disabled persons to find employment. The research questions for the subjects were the following:1. How important is it for you to enter employment?2. What knowledge of your own occupational skills do you have?3. What knowledge do you have about the possibilities of finding employment for someone with your qualifications?4. What barriers do you see that make employment difficult and result from your own limitations?5. What barriers do you see that make employment difficult and result from the specificity of the labour market?6. What hindering barriers do you see that result from provisions of the law?The idea behind all the research questions that were asked was to attempt to answer the question concerning the importance of entering employment for the study subjects. It turned out that entering employment was a priority for most of the respondents.
Keywords: disabled persons, individuals with chronic mental illnesses, barriers, entering employment